2012
DOI: 10.1111/j.1469-8986.2012.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

How about taking a low‐cost, small, and wireless EEG for a walk?

Abstract: To build a low-cost, small, and wireless electroencephalogram (EEG) system suitable for field recordings, we merged consumer EEG hardware with an EEG electrode cap. Auditory oddball data were obtained while participants walked outdoors on university campus. Single-trial P300 classification with linear discriminant analysis revealed high classification accuracies for both indoor (77%) and outdoor (69%) recording conditions. We conclude that good quality, single-trial EEG data suitable for mobile brain-computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
474
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(531 citation statements)
references
References 26 publications
(28 reference statements)
27
474
1
8
Order By: Relevance
“…Laboratory data using a mobile electroencephalography (EEG) headset (Emotiv EPOC+; validated for both laboratory and outdoor settings [17,18]) showed outputs that corresponded with self-reported measures on attractiveness, willingness to visit, valence and arousal of static images of landscapes or urban scenes [19]. This study used data from the Affectiv Suite, Emotiv proprietary software, which analyzes EEG from distinct brain activity patterns and allocates a label defining an emotional parameter ('frustration', 'excitement', 'engagement', 'meditation', 'long term excitement').…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory data using a mobile electroencephalography (EEG) headset (Emotiv EPOC+; validated for both laboratory and outdoor settings [17,18]) showed outputs that corresponded with self-reported measures on attractiveness, willingness to visit, valence and arousal of static images of landscapes or urban scenes [19]. This study used data from the Affectiv Suite, Emotiv proprietary software, which analyzes EEG from distinct brain activity patterns and allocates a label defining an emotional parameter ('frustration', 'excitement', 'engagement', 'meditation', 'long term excitement').…”
Section: Introductionmentioning
confidence: 99%
“…The EPOC system has also been successfully used to measure the response of cortical response to auditory stimulation (evoked potential, P3 component) [2,3] and visual stimulation [3,4]. The results indicated a high accuracy for ERP (event-related potential or evoked potential) peaks, ie.…”
Section: Emotiv Epoc Headset In Human-computer Interactionmentioning
confidence: 94%
“…In another study [31], Emotiv Epoc was combined with a standard infracerebral electrode cap with Ag/AgCl electrodes. The result was a low-cost portable EEG system that was tested in an auditory oddball paradigm under sitting and walking conditions.…”
Section: Related Workmentioning
confidence: 99%
“…They are mainly marketed as gaming devices and provide a limited solution to the expensive equipment problems described above: they are wirelessly connected to an ordinary computer, 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 they require a short set-up time to adjust the electrodes to the user's scalp, and they do not require conductive gel. Recent research on evaluating the reliability of some of these low-cost EEG devices for research purposes has suggested that they are reliable for measuring visual and auditory evoked potentials [Duvinage, 2013;Debener, 2012;Badcock, 2013].…”
mentioning
confidence: 99%